Pendidikan Ilmu Laduni Menurut Imam Al Ghazali - Moch Hatta; Erawadi Erawadi; Sumper Mulia Harahap (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas (STIT PL) Gunung Tua, 2024)
Education has aspects that are more complex than merely learning, teaching, or transferring knowledge. Education must have clear concepts, objectives, methodologies, and programs. Islamic education aims to develop human potential, both outwardly and inwardly, to form a fully integrated Muslim personality. Laduni knowledge is the type of knowledge obtained through divine inspiration after the purification of the soul. As explained by Imam Al-Ghazali in Ihya Ulumuddin, laduni knowledge is described as knowledge from God that directly enters the human heart without any intermediary. This knowledge is considered the most profound and full of wisdom compared to knowledge gained through ordinary learning processes. The education of laduni knowledge is inseparable from Islamic education, which is based on the Qur'an and the Sunnah. The objectives of laduni knowledge education include the formation of noble character, nurturing the soul, instilling virtues, fostering politeness, and preparing humans for both worldly and eternal life. Islamic education also balances spiritual and worldly orientations, including cultivating scientific enthusiasm and curiosity. There are two methods of acquiring knowledge: human instruction (at-ta’allum al-insaniyyah) and divine instruction (at-ta’allum ar-rabbaniyyah). Those who attain laduni knowledge tend to require little effort, face no significant difficulties in learning, and achieve great results with minimal effort.